Case detection of familial hypercholesterolemia using various criteria during an annual health examination in the workplace - Poranee Ganokroj; Suwanna Muanpetch; Nitt Hanprathet; Wiroj Jiamjarasrangsi; Weerapan Khovidhunkit (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Early diagnosis and appropriate treatment of subjects with familial hypercholesterolemia (FH) could prevent cardiovascular disease (CAD). Objective: We aimed to identify potential cases of FH during a workplace screening and to explore their clinical data. Method: Personnel who attended an annual health examination were invited to answer a questionnaire and to provide consent to review their laboratory results. FH was clinically diagnosed using any one of the three standard criteria: Dutch Lipid Clinic Network (DLCN), Simon Broome (SB), and Make Early Diagnosis to Prevent Early Deaths (MEDPED). Clinical characteristics were compared between FH and unlikely FH subjects. Results: Among 6607 participants, potential cases of FH were identified in 2.5 % by DLCN, 4.0 % by SB, and 0.8 % by MEDPED alone. Premature CAD, hypertension, and current smoking were significantly more common in potential FH subjects than in unlikely FH subjects. Potential FH subjects also had significantly higher body mass index, waist circumference, blood pressure, fasting plasma glucose and triglyceride levels than unlikely FH subjects. Among potential FH subjects, lipid-lowering medication was used in 28.4 %. The achievement of the LDL-C goal (<100 mg/dL) in potential FH subjects was significantly lower than that in unlikely FH subjects (15 % vs. 28 %, respectively, P = 0.005) despite a higher rate of high-intensity statin use (25 % vs. 10 %, respectively, P = 0.002). Conclusion: The workplace screening of FH detected a significant number of potential FH subjects with higher cardiovascular risk. This strategy identified individuals for whom intensification of both lifestyle modifications and pharmacological treatment should be a priority.